PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN YANG DIMODERASI OLEH REBRANDING PT.ABC - I Gusti Putu Putra Purnama (Journal of Economic, Bussines and Accounting (COSTING), 2025)
With the rapid development of business activities in pharmacies, companies need to adjust their strategies to ensure business sustainability, one of which is through rebranding. This effort aims to strengthen and improve the quality of service to customers. This study examines the effect of service quality on customer satisfaction and loyalty, with rebranding as a moderating variable at PT.ABC. This research involved 269 respondents who were customers who had shopped at least twice and visited the pharmacy before and after the rebranding. The sampling technique used was accidental sampling (convenience sampling). Data were analyzed using the SEM-PLS method through the SmartPLS software with a 95% confidence interval. The results showed that service quality had a positive effect on customer satisfaction (t = 3.034; p = 0.000) and customer loyalty (t = 10.043; p = 0.000). Customer satisfaction also had a positive effect on customer loyalty. Furthermore, rebranding had a positive impact on satisfaction (t = 7.996; p = 0.000) and customer loyalty (t = 4.344; p = 0.000). However, rebranding did not significantly moderate the relationship between service quality and customer satisfaction (t = 0.182; p = 0.24) or customer loyalty (t = 0.646; p = 0.52).